Presentation, Management Practices and In-hospital Outcomes of Patients with Acute Coronary Syndrome in a Tertiary Cardiac Centre in Bangladesh - Cader, Fathima Aaysha; Haq, M Maksumul; Nasrin, Sahela; Kabir, CM Shaheen (Bangladesh Heart Journal, 2018)
Background: There is no large-scale data on the management practices and in-hospital outcomes of acute coronary syndromes (ACS) in Bangladesh. This study aimed to document the presentation characteristics, treatment practices and in-hospital outcomes of ACS patients presenting to a specialized tertiary cardiac care institute in Bangladesh. Methods: This retrospective observational study included all ACS patients presenting to Ibrahim Cardiac Hospital & Research Institute (ICHRI), Dhaka, Bangladesh, over the period of January 2013 to December 2013. Data were collected from hospital discharge records and catheterization laboratory database, and analysis was carried out using Statistical Package for Social Sciences (SPSS) version 16.0 (Chicago, Illinois, USA). Result: A total of 1914 ACS patients were included. The mean age was 57.8 ± 12.1 years. 71.4% were male. 39.8% presented with ST-elevation myocardial infarction (STEMI), 39.7% with non- ST-elevation myocardial infarction (NSTEMI) and 20.5% presented with unstable angina (UA). 68.91% were diabetic, 74.24% hypertensive, 53.23% were dyslipidaemic, 25.75% were smokers and 20.72% had chronic kidney disease (CKD).1022 (53.4%) of all admitted ACS patients underwent coronary angiography, among whom 649 (33.9%) were advised percutaneous coronary intervention (PCI), and 198 (10.3%) and 207 (10.8%) were advised coronary artery bypass graft (CABG) surgery and medical management respectively. PCI was performed in 509 patients (26.6%)during the index admission. The majority of these patients were those of STEMI (39.23%), among whom 47 (6.2%) underwent primary PCI. 146 (7.6%) of the patients presenting with ACS expired during hospital stay. Mortality was highest among STEMI (10.5%), followed by NSTEMI (8.3%) and UA (1%). 501 (26.2%) patients developed left ventricular failure, 108 (5.6%) patients developed shock and 265 (13.8%) developed acute kidney injury. Conclusion: This study represents one of the larger single-centre analyses of ACS patients in Bangladesh thus far. Our patients have high prevalence of cardiovascular risk factors, particularly diabetes and hypertension. There is room for further improvement in terms of guideline-directed medical and interventional treatment modalities, in order to improve outcomes. Bangladesh Heart Journal 2017; 32(2) : 106-113